Challenges and Opportunities of Digital Transformation in Strategy Management - Suharto (International Journal of Science and Society, 2024)
Digital transformation has become a fundamental phenomenon in the business world, triggering major changes in the way companies manage their strategies. This research aims to investigate the challenges and opportunities faced by companies during the digital transformation process in the context of strategic management. This research method uses a qualitative approach with descriptive methods. Overall, digital transformation in corporate strategic management brings a number of challenges involving change resistance, information security, technological uncertainty, costs and investments, regulatory compliance, dependence on data, skills gaps, as well as opportunities involving increased operational efficiency, better access to data, increased innovation, more personalized customer interactions, increased information security, operational cost savings, provision of better UI/UX interfaces, flexibility and adaptability, increased competitiveness, and expansion of markets and business models. To overcome these challenges, companies need to take proactive steps such as effective communication, investment in cybersecurity, employee training, and wise cost management. Meanwhile, taking advantage of these opportunities requires a focus on innovation, developing employee skills, and strategies that are adaptive to market changes. Digital transformation, if managed well, can be a key driver for growth, competitive advantage and business sustainability in this digital era.